SINDICATO DOS PROFESSORES DA REDE PÚBLICA DE EDUCAÇÃO DO ESTADO DE SÃO PAULO: COMO VAI O MOVIMENTO NA ERA NEOLIBERAL? - Nascimento, Cleusa de Jesus do (2010)
The sociopolitical study from there present, analyzes the absence of participation of teachers from public school, in São Paulo, Brazil, in trade union movements, since the decade of 2000. The career s devaluation and low salaries remain been complaints similar to the past; the difference is that there is no more movement as in the past. To find such inertia we start the observation of teachers participation in trade union movements from 1980 until 2009, dividing in two periods: the first one, from 1980 to 1989 and 1990 to 1999, (because in them, occur the largest category s movements), and the second period from 2000 to 2009 (where there is a clear decline of such movements).The second period since 2000 to 2009 (where we can observe clearly, the decline of movements).The aim of this research is an answer that explain why teachers, nowadays, don t participate of syndical movements and cause the absence of teachers in movements of category. We will do the research with two generations of different teachers that have ingressed since 2000. The hypothesis studied the differences of the origin of social group of teachers, their political formation and their university formation inside the neoliberal pattern and neoliberal politics adopted in basic public schools in São Paulo, were the way that influenced the level of participation of the teachers in syndical movements, causing differences of revendicate behaviour among the generations. This research doesn t aim to analyze the syndicates, but the thinking and feeling of elements that form these syndicates and form the soul of thinking and feeling of movements that form the teachers.